Pembinaan Keberagamaan Siswa Muslim di SMA Don Bosco Padang - Anita, Febi; Satria, Rengga (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Religion is the condition of religious adherents in reaching and practicing religious recommendations in their life activities, belief in Allah SWT with teachings and the obligation to carry out worship for religion. This study aims to find out how the religious development of Muslim students at Don Bosco Padang High School. This research uses qualitative methods with a phenomenological approach. Data sources were taken from twelve informants through in-depth interviews selected using purposive sampling techniques. The twelve informants were one Islamic education teacher, one school principal and ten students. To obtain research data, researchers use a set of interview guidelines and observation guidelines as research instruments. Data collection techniques used in this research are observation, interviews and documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation and conclusions. The results showed that there are several forms of religious development activities for Muslim students carried out at Don Bosco Padang High School, namely praying before studying and after studying, congregational dhuhur prayers, cults, youth wirid and commemorating Islamic holidays.